GETTING TEXTURED SURFACES OF POLYMER MATERIALS USING METAL TEMPLATES - СТРАШЕНКО, В. К.; МИРОНЮК, О. В. (Technologies and Engineering, 2024)
Objective. To compare the structure and water repellent properties by determining the wetting angle of textured surfaces using metal master molds for making samples through various methods. Methodology. The structure of surfaces obtained through different manufacturing methods, namely templating method, filling the template with monomer followed by polymerization, and applying polymer and solvent solution followed by removal of the liquid medium, is studied using optical microscopy. The regularity of the structure was analyzed by digital images taken with optical microscopy. Water repellent properties were investigated using the sessile drop method with a goniometric attachment. Results. Textured surfaces were produced from various materials, including low-density polyethylene, polydimethylsiloxane rubber, and ethylene-propylene rubber. The methods used for their production are indicated. The qualitative characteristics of each surface, considering the template geometry, are described. A quantitative analysis of the wetting angle values of textured and non-textured surfaces was conducted. The causes and consequences of the deterioration in sample properties are supplemented, along with proposed methods for their resolution. Scientific novelty. Using optical microscopy to establish the optimal method for fulfilling one of the key conditions for producing textured surfaces. By utilizing a metal template, specifically aluminum, templates from other materials were created. Additionally, determining the quantitative impact of surface texturing on selected materials without fulfilling two other criteria. Practical significance. The described methods can be applied to scale up the process of manufacturing textured surfaces using lighter methods and a variety of materials.